New Evidence on Real Earnings Management: An International Investigation - Wang, Xuejun (Auckland University of Technology, 2014)
Real earnings management has attracted increasing attention in accounting research (Roychowdhury, 2006; Cohen et al., 2008; Gunny, 2010; Zang, 2012). However, real earnings management has still received relatively light testing and inconsistency and conflicts exist in existing evidence in relation to real earnings management. In addition, as most of the existing studies on real earnings management focuses on testing large economies, such as in the U.S., these studies have failed to provide findings on real earnings management in an international context. Therefore, the objective of this thesis is to test firms’ real earnings management in different institutional environments and crisis periods, and the relationship between real earnings management activities and firms’ future performance. Utilising a sample of 135,722 firm-year observations for 31 countries from 1996 to 2011, this thesis finds more income-increasing real earnings management behaviours in countries with a code-law tradition, a French-civil-law tradition, lower investor protection, lower law enforcement, and countries with more concentrated ownership. The results also show a significant negative association between firms’ real earnings management activities and firms’ future ROA (return on assets) and future CFO (cash flow from operations). And in terms of this negative impact of REM (real earnings management) on firms’ future cash generating ability, it is moderated by a stronger institutional environment. In addition, this thesis documents a negative association between REM and CRISIS. In regard to the results on the sub-components of REM, the result show that in crises, firms engage in sales manipulation and reduction of discretionary expenses to increase reported earnings. And the negative impacts of REM on firms’ future ROA and future CFO is found to reduce during crises.
Keywords: Real earnings management; Institutional environment; Financial crisis